THE EFFECT OF CALCITONIN IN LOMBER SPINAL STENOSIS - Özlem Levent,; Burcu Yanık,; Şehim Kutlay,; Süreyya Ergin, (Archives of Rheumatology, 2003)
Lomber spinal stenosis is a chronic degenerative syndrome which come out from pressure on neural structures by stenotic spinal canal or intervertebral foramen and is characterized by neurogenic claudication clinically. Education of the patient is very important, treatment choices are conservative approaches such as physical therapy, epidural enjections, calcitonin therapy and surgical decompression operations. 41 patients diagnosed as lomber spinal stenosis clinically and radiologically were taken to the study. Patients were randomized into two groups. In the first group (n=20), the patients were included in a physical therapy program. The second group (n=21) took salmon calcitonin 100 IU daily for 15 days, in addition to the physical therapy. The patients were evaluated two times, initially and 2 months later. In conclusion, intensity of pain decreased and lumbar range of motion increased in both of the groups. There was improvement in paresthesia in the calcitonin group.There was no significant improvement in walking distance in both of the groups. According to these results, calcitonin therapy is found effective as and can be used safely in patients with lumbar spinal stenosis.